A new paradigm evaluating cost per cure of HCV infection in the UK. Issue 1 (December 2016) - Barclay, Stephen; Cooke, Graham; Holtham, Elizabeth; Gauthier, Aline; Schwarzbard, Jeremie; Atanasov, Petar; Irving, William
Abstract Background New interferon (IFN)-free treatments for hepatitis C are more effective, safer but more expensive than current IFN-based therapies. Comparative data of these, versus current first generation protease inhibitors (PI) with regard to costs and treatment outcomes are needed. We investigated the real-world effectiveness, safety and cost per cure of 1st generation PI-based therapies in the UK. Methods Medical records review of patients within the HCV Research UK database. Patients had received treatment with telaprevir or boceprevir and pegylated interferon and ribavirin (PR). Data on treatment outcome, healthcare utilisation and adverse events (AEs) requiring intervention were collected and analysed overall and by subgroups. Costs of visits, tests, therapies, adverse events and hospitalisations were estimated at the patient level. Total cost per cure was calculated as total median cost divided by SVR rate. Results 154 patients from 35 centres were analysed. Overall median total cost per cure was £44, 852 (subgroup range, : £35, 492 to £107, 288). Total treatment costs were accounted for by PI: 68.3 %, PR: 26.3 %, AE management: 5.4 %. Overall SVR was 62.3 % (range 25 % to 86.2 %). 36 % of patients experienced treatment-related AEs requiring intervention, 10 % required treatment-related hospitalisation. Conclusions This is the first UK multicentre study of outcomes and costs of PI-based HCV treatments in clinical practice. There was substantial variation in total cost per cure among patient subgroups and high rates of treatment-related discontinuations, AEs and hospitalisations. Real world safety, effectiveness and total cost per cure for the new IFN free combinations should be compared against this baseline.